Festival as an agent for behavior change: a study of garden festival in Malaysia - Ibrahim, Nora; Ismail, Nor Atiah; Mohd Yunos, Mohd Yazid; Utaberta, Nangkula; Mohd Ariffin, Noor Fazamimah; Ismail, Sumarni (Faculty of Design & Architecture, Universiti Putra Malaysia, 2015)
A number of studies have been conducted to examine tourists’ behavior. However, there has been little research conducted to study on visitors’ behavior in the garden festival. Today, festival is the one of the fastest growing in tourism industries in Malaysia. Festival as a vehicles for behavior change who visit them. This paper examines visitors’ involvement at the festival and provides an integrated approach to understand the effect of the visitors behavior based on the perceived value and satisfaction as relates to their behavior intention to revisit and construct own garden using the modified theory of reasoned action (TRA). The purpose of this study is to examine the effects of perceived value on intention to revisit and construct own garden, satisfaction, and satisfaction on intention to revisit and construct own garden. Results indicated that the perceived value of garden showcase at garden festival are good predictors of visitors behavior change. Thus, the most significant contribution of this study is a theoretical understanding with empirical results using the new factors of perceived value of garden festival, satisfaction and behavior intention to revisit and construct own garden in the contact of the modified TRA. This will be useful for garden festival organizers as well as marketing organization.